India's Assisted Reproduction Bill and the Materna Surrogacy Industry - Deonandan, Raywat; Bente, A (Université d'Ottawa | University of Ottawa, 2012)
The latest version of India's assisted reproduction bill addresses many of the shortfalls of the previous draft. In this paper, we examine the latest draft's failure to address the most preponderant ethical issues affecting the burgeoning reproductive tourism industry
Keywords: assisted reproduction; surrogacy; ethics; law; epidemiology